1985
DOI: 10.1128/iai.50.3.860-868.1985
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of human choriogonadotropin-like material in coagulase-negative Staphylococcus species

Abstract: We identified 101 coagulase-negative Staphylococcus strains obtained from different laboratories, the American Type Culture Collection, and our collection, isolated from 23 patients with overt cancer and 34 normal individuals through Kloos and Schleifer conventional methods and the Staph-Ident staphylococcal system (Analytab Products, Plainview, N.Y.). In 40 strains, identity was further verified by DNA-DNA hybridization techniques. Identification revealed 39 S. epidermidis, 22 S. hominis, 8 S. haemolyticus, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…These antibodies were immunologically similar to the antibodies produced by hCG, since we found that the antibodies to the bacteria containing the hCG-like material also cross-reacted with hLH (Table 1). The data also demonstrated that the bacterial material could be extracted by disruption of the cell membranes and that the expression of the hCG-like protein by bacteria is a strain characteristic and not a species characteristic, confirming the results from our immunocytochemical studies (1). Bacteria within the same species shown by immunocytochemistry to be devoid of the hormone-like protein (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These antibodies were immunologically similar to the antibodies produced by hCG, since we found that the antibodies to the bacteria containing the hCG-like material also cross-reacted with hLH (Table 1). The data also demonstrated that the bacterial material could be extracted by disruption of the cell membranes and that the expression of the hCG-like protein by bacteria is a strain characteristic and not a species characteristic, confirming the results from our immunocytochemical studies (1). Bacteria within the same species shown by immunocytochemistry to be devoid of the hormone-like protein (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Peroxidase staining was done with 3-amino-9-ethlycarbazole (Sigma Chemical Co., St. Louis, Mo.). This bacterial strain has also shown reactivity with another monoclonal antibody to hCG, that reacts with an epitope different to the one reacting with antibody 337W, and with polyclonal antisera to whole hCG, to hCGI3, to the hCG, COOH-terminal peptide residues 115 through 145, and to hCGcx (1). Streptococcus bovis AV46 has also shown a positive reaction with the same reagents.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Unicellular organisms like bacteria and yeasts have been identified to acquire genes of certain hormones. Of fundamental importance is the fact that some bacteria isolated from cancer patients expressed hCG, but not every isolated bacteria did (28–33). Moreover, the morphologic changes observed by electron microscopy (34) indicated that some of the bacteria expressing the hCG‐like material are revertants of cell wall deficient (CWD) variants.…”
Section: Introductionmentioning
confidence: 99%